Effects of public data open on performance of government functions in China: the roles of digital economy and market economic system adopting the perspective of resource- based view - Zhang, Diandian; Mu, Zijian; Tan, Zhiqian (Frontiers in Political Science, 2024)
IntroductionThe emergence of the digital economy necessitates effective government guidance and regulation of enterprise behavior to ensure fair market competition. Understanding how public data open can enhance the performance of government functions is crucial, particularly in understanding the roles of key factors like the development of the digital economy and the current state of the market economic system. This study explores the effects of public data open on performance of government functions from a resource-based perspective.MethodsUsing a dataset of 237 Chinese cities from 2017 to 2021, we employed a two-way fixed-effects model to investigate the mechanisms. This includes its interaction with the development of the digital economy and the moderating role of the market economic system.ResultsThe findings reveal that public data open significantly improves performance of government functions, as validated by a multi-temporal DID model and various robustness checks. Notably, the development of the digital economy mediates this relationship, while the market economic system has a strong positive moderating effect. The effects of public data open on performance of government functions also exhibits significant variability.DiscussionRecommendations include coordinating regional public data open resource planning and allocation, enhancing public data open rules and objectives by region, and promoting synergy between public data open, development of digital economy and the market economic system.